2010
DOI: 10.1074/jbc.m110.102277
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Brain β-Amyloid (Aβ) by Fluvastatin, a Hydroxymethylglutaryl-CoA Reductase Inhibitor, through Increase in Degradation of Amyloid Precursor Protein C-terminal Fragments (APP-CTFs) and Aβ Clearance

Abstract: Epidemiological studies suggest that statins (hydroxymethylglutaryl-CoA reductase inhibitors) could reduce the risk of Alzheimer disease. Although one possible explanation is through an effect on ␤-amyloid (A␤) metabolism, its effect remains to be elucidated. Here, we explored the molecular mechanisms of how statins influence A␤ metabolism. Fluvastatin at clinical doses significantly reduced A␤ and amyloid precursor protein C-terminal fragment (APP-CTF) levels among APP metabolites in the brain of C57BL/6 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 61 publications
6
72
0
2
Order By: Relevance
“…Studies have shown fluvastatin unable to cross BBB (Guillot et al, 1993) but effective in protecting BBB integrity (Kuhlmann et al, 2008) in nontransgenic mice. Consistent with these results, it was reported that fluvastatin decreased endogenous A levels through an increase in A clearance at BBB in nontransgenic mice (Shinohara et al, 2010). In addition, thus far, there was no report that fluvastatin reduces brain cholesterol levels.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Studies have shown fluvastatin unable to cross BBB (Guillot et al, 1993) but effective in protecting BBB integrity (Kuhlmann et al, 2008) in nontransgenic mice. Consistent with these results, it was reported that fluvastatin decreased endogenous A levels through an increase in A clearance at BBB in nontransgenic mice (Shinohara et al, 2010). In addition, thus far, there was no report that fluvastatin reduces brain cholesterol levels.…”
Section: Introductionsupporting
confidence: 75%
“…However, it is still unclear by which mechanism fluvastatin regulated the expression of A PP and A PP-cleaving enzymes, ultimately resulted in the reduction of brain A levels without entering into the brain. It was reported that fluvastatin decreased endogenous A levels through an increase in A clearance at BBB in nontransgenic mice (Shinohara et al, 2010). Besides, reduction of NO levels by inhibiting the enzyme catalyzed NO biosynthesis, endothelial nitric oxide synthase (eNOS), or by knocking eNOS gene out led to increased A PP and BACE1 protein levels, as well as increased secretion of A in brain microvascular endothelial cells (Austin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A produção de beta-amiloide pode acontecer em uma ampla gama de compartimentos celulares como na superfície celular, rede trans-Golgi e nos endossomos (De Strooper, 2000), bem como pode ser consequência de um processo inflamatório característico da doença de Alzheimer, com a participação da prostaglandina E2 e seu receptor EP4 (Shinohara et al, 2010).…”
Section: Discussionunclassified
“…Logo o processo inflamatório favorece a formação de beta-amiloide, mas na presença de Rab 5 esse quadro é revertido nos neurônios (Shinohara et al, 2010), pois a prostaglandina é inibida, diminuindo a atividade da gamasecretase, e consequentemente a produção de beta-amiloide (Hoshino et al, 2009). Nesse trabalho os níveis de Rab 5 parecem não favorecer a possível recaptura da beta-amiloide, e ao mesmo tempo esses baixos níveis podem contribuir para produção do peptídeo beta-amiloide intracelularmente, além de também contribuírem para prejudicar a manutenção de endossomos gerais que estão ligados a outras funções neuronais como reciclagem de vesículas sinápticas Postula-se a hipótese de que as vesículas sinápticas devem sofrer um processo de maturação para tornarem-se funcionais no terminal sináptico (Bonanomi et al, 2006).…”
Section: Discussionunclassified